Digital Intimacy in Real Time: Live Streaming Gender and Sexuality. (July 2022) - Ruberg, Bo; Brewer, Johanna
This article serves as the guest editors' introduction to the Television and New Media special issue dedicated to gender and sexuality in live streaming. Live streaming is a key part of the contemporary digital media landscape; it sits at the center of wide-reaching shifts in how culture, entertainment, and labor are expressed and experienced online today. Gender and sexuality are crucial elements of live streaming. Across live streaming's many forms, these elements manifest in myriad ways: from gendered performances to gender-based harassment, from LGBTQ community building to real-time sex work. This special issue models an interdisciplinary approach to studying gender and sexuality in live streaming, featuring scholarship from the humanities, social sciences, and human-computer interaction. It also serves as an impassioned call to those who study technological tools and platforms like live streaming to pay attention to the crucial roles that identity, power, embodiment, and intimacy play in these technologies. There can be no full cultural understanding of live streaming that does not address its entanglements with sexuality and gender.